HUBUNGAN PENGETAHUAN REMAJA PUTRI TENTANG PERUBAHAN FISIK PUBERTAS DENGAN SIKAP MENGHADAPI PUBERTASDI UNIVERSITAS MUHAMMADIYAH BANJARMASIN - Yaolanda Rizqi Agustina; Bardiati Ulfah, Noor Anisa, Suryati, Mutia Aura Nazwa Assyfa (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2025)
Background: Puberty is a period of change or developmental stage from childhood to adulthood which includes biological changes, psychological changes, and psychosocial changes in the way they think, make decisions, and interact with the world around them. Objective: To Relate Knowledge of Adolescent Girls About Physical Changes in Puberty With Attitudes Facing Puberty at University of Muhammadiyah Banjarmasin. Research Method: This type of research is descriptive analytical, with a cross-sectional approach. Data analysis technique using Kendall Tau correlation. Research Results:  From  this  study,  the  results  obtained  were significant values between knowledge and attitudes with a p- value of 0,255 > 0,05. Conclusion: There is no relationship between adolescent girls' knowledge of physical changes in puberty during puberty with attitudes towards puberty. Good adolescent knowledge and attitudes towards physical changes during puberty should be maintained and improved again to understand health, especially reproduction in adolescents,  which  allows  someone  to  adapt  to  their  environment and be able to solve the problems they face.